2005
DOI: 10.1037/0278-7393.31.1.3
|View full text |Cite
|
Sign up to set email alerts
|

When Does Feedback Facilitate Learning of Words?

Abstract: Some researchers have suggested that although feedback may enhance performance during associative learning, it does so at the expense of later retention. To examine this issue, subjects (N = 258) learned Luganda-English word pairs. After 2 initial exposures to the materials, subjects were tested on each item several times, with the presence and type of feedback varying between subjects. A final test followed after 1 week. Supplying the correct answer after an incorrect response not only improved performance du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
348
3
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(384 citation statements)
references
References 25 publications
(40 reference statements)
22
348
3
4
Order By: Relevance
“…The testing effect is the phenomenon that retrieval practice leads to better long-term retention than additional study (for reviews see e.g., Rawson & Dunlosky, 2011;Roediger & Butler, 2011;Roediger, Putnam, & Smith, 2011;Roediger & Karpicke, 2006;Rowland, 2014). As in the studies conducted on distributed practice, most experiments on retrieval practice have been conducted using word lists or word pairs (e.g., Bouwmeester & Verkoeijen, 2011;Carpenter, Pashler, & Vul, 2006;Carpenter, Pashler, Wixted, & Vul, 2008;Toppino & Cohen, 2009;Tulving, 1967;Wheeler, Ewers, & Buonanno, 2003) and foreign vocabulary pairs (e.g., Carpenter et al, 2008;Carrier & Pashler, 1992;Fritz, Morris, Acton, Voelkel, & Etkind, 2007;Karpicke, 2009;Karpicke & Roediger, 2008;Pashler, Cepeda, Wixted, & Rohrer, 2005;Pyc & Rawson, 2007Toppino & Cohen, 2009). Some studies have found a beneficial effect of retrieval practice for first language vocabulary learning, with adults (e.g., Cull, 2000;Karpicke & Smith, 2012), as well as with primary school children (e.g., Goossens, Camp, Verkoeijen, Tabbers, & Zwaan, 2014;Metcalfe, Kornell, & Son, 2007).…”
mentioning
confidence: 99%
“…The testing effect is the phenomenon that retrieval practice leads to better long-term retention than additional study (for reviews see e.g., Rawson & Dunlosky, 2011;Roediger & Butler, 2011;Roediger, Putnam, & Smith, 2011;Roediger & Karpicke, 2006;Rowland, 2014). As in the studies conducted on distributed practice, most experiments on retrieval practice have been conducted using word lists or word pairs (e.g., Bouwmeester & Verkoeijen, 2011;Carpenter, Pashler, & Vul, 2006;Carpenter, Pashler, Wixted, & Vul, 2008;Toppino & Cohen, 2009;Tulving, 1967;Wheeler, Ewers, & Buonanno, 2003) and foreign vocabulary pairs (e.g., Carpenter et al, 2008;Carrier & Pashler, 1992;Fritz, Morris, Acton, Voelkel, & Etkind, 2007;Karpicke, 2009;Karpicke & Roediger, 2008;Pashler, Cepeda, Wixted, & Rohrer, 2005;Pyc & Rawson, 2007Toppino & Cohen, 2009). Some studies have found a beneficial effect of retrieval practice for first language vocabulary learning, with adults (e.g., Cull, 2000;Karpicke & Smith, 2012), as well as with primary school children (e.g., Goossens, Camp, Verkoeijen, Tabbers, & Zwaan, 2014;Metcalfe, Kornell, & Son, 2007).…”
mentioning
confidence: 99%
“…However, different types of feedback are not equivalently effective (Fazio, Huelser, Johnson, & Marsh, 2010;Pashler et al, 2005). Most research has demonstrated that feedback is especially effective when the correct response is shown (correct answer feedback).…”
Section: Feedbackmentioning
confidence: 99%
“…Thus, because correct answer feedback provides both diagnostic information and information necessary to update memory, it is generally more effective than right/wrong feedback (Fazio et al, 2010;Pashler et al, 2005).…”
Section: Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, feedback that includes a presentation of the correct response is much more effective than simply indicating that a response is right or wrong (e.g., Pashler, Cepeda, Wixted, & Rohrer, 2005). Accordingly, the standard way to present feedback is simply to show the correct answer to students.…”
mentioning
confidence: 99%